Preparation method of low-component ammonia-free impregnated activated carbon adsorbent of CNCl
The suitable metal active components are screened through quantum chemometry, and the preparation method of ammonia-free metal impregnated activated carbon is solved, and the problems of ammonia gas escape and complex process in the prior art are realized, and the preparation of impregnated activated carbon for metal nanoparticle active components with low components and high dispersion is maintained, maintaining high protection ability and economicality.
Patent Information
- Application Number
- CN202411019901.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2025-03-28
AI Technical Summary
Existing impregnated activated carbon used to remove military poison CNCL usually uses a large amount of metal substances and a solution containing ammonium bicarbonate and ammonia water, which causes ammonia to escape, causing secondary damage to the user, and the process is complex and costly.
By quantum chemistry calculating the adsorption and reaction energy of the associated metal active components and cyanochloride adsorption and reaction energy, suitable preparation methods for low-component ammonia-free metal impregnated activated carbon were screened out, and water-soluble metal salts and sodium borohydride reducing agents were used to deposit metal active components in a directional manner, avoiding the use of ammonium bicarbonate and ammonia water.
The preparation of impregnated activated carbon for metal nanoparticle active components with low components and high dispersion is realized, which avoids ammonia escape, simplifies the process, reduces the metal load, and maintains high protection ability, and has a high protective effect on CNCL.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the field of adsorbent preparation, and in particular to a method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl. Background Art
[0002] As a cyanogen poison, cyanogen chloride is often used in military warfare due to its strong toxicity and rapid action. At the same time, cyanogen chloride has a small molecular weight and a large saturated vapor pressure, so its vapor is not easy to be adsorbed. Therefore, in the actual protection process, metals or metal compounds are usually used to impregnate activated carbon to enhance the adsorption and elimination ability of activated carbon to cyanogen chloride vapor. Metal-impregnated activated carbon has been used in the military to remove toxic warfare agents for decades. The adsorbent is treated by impregnating activated carbon in an ammonia solution of basic copper carbonate. The treated activated carbon is heated to 150°C or even higher. The basic copper carbonate in the activated carbon pores decomposes into copper oxide and releases carbon dioxide and ammonia. U.S. Patent US 5,063,196 discloses "a chromium-free impregnated activated carbon for adsorbing harmful gases", the main components of which are Cu 4-14%, Zn2-12%, Ag 0-1% and triethylenediamine 1.5-6%, which is mainly used for military protection against toxic gases such as HCN and CNCL. At present, the most widely used impregnated carbon in gas mask canisters and protective equipment is ASC-T and ASZM-T impregnated carbon, and the loaded active components are copper, chromium, silver and copper, molybdenum, zinc, and silver. However, most of this impregnated carbon uses ammonia water as a solvent for metal compounds. The ammonia smell cannot be completely removed during the later heating, and there will be irritating odors such as ammonia during use, which has become a major problem for current military protective adsorption materials. Therefore, it is very important to find a method for preparing impregnated activated carbon that does not use ammonium bicarbonate and ammonia water, which may cause the release of ammonia molecules. For example, the patent application number CN202111058583.X, "A green preparation method for ammonia / chromium-free impregnated activated carbon adsorbent for user protection HCN / CNCL", mainly introduces a method in which a water-soluble metal precursor component is synergistically loaded on the activated carbon and then treated with a certain concentration of catechol solution, and then filtered, washed, low-temperature dried and programmed temperature is activated to prepare ammonia-free and chromium-free impregnated activated carbon. However, this method is complex and requires high-temperature activation in the later stage.
[0003] From the above domestic and foreign public literature and background descriptions, it can be seen that most of the impregnated activated carbons used to remove the classic military poison CNCL at home and abroad use copper, tungsten, vanadium, iron, molybdenum, zinc, cobalt, nickel and other metal substances, and the metal addition amount can reach 20%-50%. There are many types of metal additions, large addition amounts, and complex addition systems, which greatly increase the complexity and economic cost of the preparation process of impregnated activated carbon. In addition, most of the preparation methods in public literature use ammonium bicarbonate and ammonia water as the dissolving liquid of the metal active component precursor. There is a problem of residual ammonia escape during use, causing secondary harm to the users. Although many researchers have begun to devote themselves to the research of ammonia-free impregnated carbon, that is, ammonia water is not used as a solvent during the impregnation process, and ammonium compounds such as ammonium bicarbonate are not added to reduce the escape of ammonia smell in the later stage, this method often requires a higher temperature for activation treatment, which will complicate the preparation process. Summary of the invention
[0004] The present invention overcomes the deficiencies of the prior art and provides a method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl. The present invention uses quantitative calculation to associate the intrinsic properties of metals with the adsorption energy and reaction energy of small molecules of cyanogen chloride and its intermediates, screens metal active components based on the calculation results, and provides a method for preparing a low-component ammonia-free metal impregnated activated carbon. This preparation method reduces the metal loading while not using substances such as ammonium bicarbonate and ammonia water that are easy to release ammonia, and will not cause the later ammonia to escape from the activated carbon pores to cause secondary injuries to users, and at the same time has a high protection capability for CNCL.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl, comprising the following steps:
[0006] a) Screening of metal active components
[0007] Quantum chemical calculations are used to correlate the relationship between the intrinsic properties of the metal active component surface, such as electronic structure and geometric structure, and the adsorption and reaction energy of cyanogen chloride and its intermediate small molecules, to obtain the optimal reaction substrate for cyanogen chloride hydrolysis reaction and to screen active components;
[0008] The electronic descriptor ψ is used to describe the electronic structure of different metal substrates, and the formula is as follows:
[0009]
[0010] S v is the valence electron, and χ is the electronegativity. The electronic descriptor ψ effectively reflects the d-band characteristics of metals and can be used to describe the electronic structure of substrates such as pure metals, clusters, alloys, and oxides;
[0011] The generalized coordination number is used to describe the geometric structure of different surfaces. The formula for calculating the generalized coordination number is as follows:
[0012]
[0013] n is the number of the nearest neighbors of the central atom, i is the i-th nearest neighbor atom around the central atom, CN(i) is the common coordination number of the i-th atom, that is, the number of the nearest neighbors around the i-th atom, CN max is the maximum coordination number (for fcc structure, CN max =12; for bcc structure, CN max =8). The generalized coordination number represents the atomic packing density of atoms on the free surface and can effectively describe the geometric structure of the metal surface.
[0014] Combining the electronic descriptor ψ and the generalized coordination number By understanding the adsorption and reaction characteristics of small molecules on metal surfaces, as well as the effects of changes in electronic and geometric structures, the present invention ultimately determined that Cu surfaces (such as Cu(110), Cu(221), and Cu(532)) and Au step surfaces are suitable substrates for the hydrolysis of cyanogen chloride.
[0015] b) Preparation of low-component ammonia-free impregnated activated carbon adsorbent
[0016] b1) Based on the mass of the porous activated carbon carrier, weigh a certain amount of active components, add them into deionized water and stir them thoroughly to dissolve, then add the porous activated carbon and stir evenly;
[0017] b2) preparing a sodium borohydride solution, adding it dropwise to the solution in step b1), and stirring at room temperature for 1-4 hours, then filtering the activated carbon and washing it with deionized water for 1-3 times, and then drying;
[0018] b3) The dried impregnated activated carbon is washed with nitric acid solution for 1-3 times and then washed with deionized water until neutral, and then dried to obtain a low-component ammonia-free impregnated activated carbon adsorbent of CNCl.
[0019] As a further limitation of the technical solution of the present invention, in step a), the Cu surface and the step surface of Au are determined to be suitable substrates for hydrolysis of cyanogen chloride.
[0020] As a further limitation of the technical solution of the present invention, in step b1), the active component is copper nitrate or chloroauric acid, wherein the added amount of copper nitrate is 3%-10% of the mass of the porous activated carbon carrier, and the added amount of chloroauric acid is 1%-2% of the mass of the porous activated carbon carrier; the amount of deionized water is 400%-1600% of the mass of the porous activated carbon carrier.
[0021] As a further limitation of the technical solution of the present invention, the concentration of the sodium borohydride solution in step b2) is 0.5 mol / L, and the volume ratio of the sodium borohydride solution to the mixed solution in step b1) is 25-100:1.
[0022] As a further limitation of the technical solution of the present invention, the drying conditions of step b2) and step b3) are both 60-80° C. for 12-24 hours.
[0023] As a further limitation of the technical solution of the present invention, the concentration of the nitric acid solution in step b3) is 1 mol / L.
[0024] As a further limitation of the technical solution of the present invention, the active component copper nitrate in step b1) is replaced by copper sulfate, copper acetate or copper chloride.
[0025] As a further limitation of the technical solution of the present invention, the porous activated carbon is wood activated carbon, coal-based activated carbon, asphalt-based spherical activated carbon or phenolic resin-based activated carbon.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention obtains the directional relationship between the intrinsic properties of the metal active component and the adsorption and reaction of small molecules in the hydrolysis reaction of cyanogen chloride through quantum chemical calculation. Based on the screening of the metal active component, the metal compound precursor materials are all selected as water-soluble metal salts. The metal active component is directional deposited into the activated carbon pores by adding sodium borohydride reducing agent to the metal precursor solution, and then washed and low-temperature dried to prepare the impregnated activated carbon with low-component and highly dispersed metal nanoparticle active components. The impregnated activated carbon for protecting CNCL obtained by this preparation method has good chemical adsorption catalytic activity, does not use ammonium bicarbonate and ammonia water and other substances that are easy to release ammonia, and will not cause the situation of late ammonia escaping from the activated carbon pores to cause secondary damage to the user. At the same time, this preparation method is simple in process, safe and controllable, has low metal loading content, high activity, maintains the protective ability of the impregnated carbon CNCL, and has certain practicality and economy. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments.
[0029] Example 1
[0030] 1) Weigh 1.5 g of copper nitrate and dissolve it in 400 ml of deionized water, then add 50 g of crushed coconut shell activated carbon, and stir and mix thoroughly at room temperature;
[0031] 2) Weigh 0.3 g of sodium borohydride, then add 15.8 g of deionized water and stir continuously until dissolved;
[0032] 3) Slowly drop the sodium borohydride solution of step 2) into the activated carbon solution of step 1), stir at room temperature for 4 hours, and finally wash with deionized water and dry at 60° C. for 12 hours.
[0033] Example 2
[0034] 1) Weigh 1.5 g of copper nitrate and dissolve it in 400 ml of deionized water, then add 50 g of crushed coconut shell activated carbon, and stir and mix thoroughly at room temperature;
[0035] 2) Weigh 0.3 g of sodium borohydride, then add 15.8 g of deionized water and stir continuously until dissolved;
[0036] 3) Slowly drop the sodium borohydride solution of step 2) into the activated carbon solution of step 1), stir at room temperature for 4 hours, and finally wash with deionized water and dry at 60° C. for 12 hours.
[0037] 4) The metal-impregnated activated carbon obtained in step 3) was placed in 400 ml of 1 mol / L nitric acid solution and stirred for 10 min, then washed with deionized water until neutral, and dried at 60° C. for 12 h.
[0038] Example 3
[0039] 1) Weigh 1g of chloroauric acid and dissolve it in 400ml of deionized water, then add 50g of crushed coconut shell activated carbon, and stir and mix thoroughly at room temperature;
[0040] 2) Weigh 0.1 g of sodium borohydride, then add 5.3 g of deionized water and stir continuously until dissolved;
[0041] 3) Slowly drop the sodium borohydride solution of step 2) into the activated carbon solution of step 1), stir at room temperature for 4 hours, and finally wash with deionized water and dry at 60° C. for 12 hours.
[0042] Comparative Example 1
[0043] 1) Take a solvent (ammonia water) in an amount of (90-100)% of the water volume of the activated carbon, heat the solution, and add 5% of ammonium bicarbonate and 15% of basic copper carbonate while stirring to fully dissolve;
[0044] 2) Weigh 50 g of coconut shell crushed carbon, impregnate the activated carbon with the solution dissolved in step 1), and dry and calcine in a flowing air flow at 140° C. for 12 h;
[0045] Comparative Example 2
[0046] 1) Take a solvent (ammonia water) according to the water volume of (90-100)% of the mass of the activated carbon, heat the solution, and add 1% ammonium bicarbonate and 3% basic copper carbonate while stirring to fully dissolve;
[0047] 2) Weigh 50 g of coconut shell crushed carbon, impregnate the activated carbon with the solution dissolved in step 1), and dry and calcine in a flowing air flow at 140° C. for 12 h;
[0048] The materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were tested and evaluated for the protection time and metal loading content of cyanogen chloride.
[0049] Cyanogen chloride: specific speed 0.25L / min·cm 2 , height 2cm, test air flow temperature (15-30)℃, relative humidity (50±2)%, initial cyanogen chloride concentration 9.0mg / L.
[0050] Table 1 Activated carbon impregnation cyanogen chloride protection time and metal loading
[0051]
[0052] From Table 1, it can be seen that the metal loading content of the ammonia-free impregnated activated carbon prepared in the embodiment is all below 1%, which is 90%-97% less than that of the ammonia-containing impregnated carbon, while maintaining the protective performance of the ammonia-containing impregnated carbon against cyanogen chloride at high metal content. The present invention uses quantitative calculation to associate the intrinsic properties of the metal with the adsorption energy and reaction energy of small molecules of cyanogen chloride and its intermediates, screens the metal active components based on the calculation results, and provides a preparation method for low-component ammonia-free metal impregnated activated carbon. This preparation method reduces the metal loading while not using substances such as ammonium bicarbonate and ammonia water that are easy to release ammonia, and will not cause the later ammonia to escape from the activated carbon pores to cause secondary injuries to the user, while maintaining the protective ability of the impregnated carbon CNCL.
Claims
1. A method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl, characterized in that: The following steps are involved: a) Screening of metal active components Quantum chemical calculations are used to correlate the relationship between the intrinsic properties of the metal active component surface, such as electronic structure and geometric structure, and the adsorption and reaction energy of cyanogen chloride and its intermediate small molecules, to obtain the optimal reaction substrate for cyanogen chloride hydrolysis reaction and to screen active components; The electronic descriptor ψ is used to describe the electronic structure of different metal substrates, and the formula is as follows: S v is the valence electron, χ is the electronegativity; The generalized coordination number is used to describe the geometric structure of different surfaces. The formula for calculating the generalized coordination number is as follows: n is the number of the nearest neighbors of the central atom, i is the i-th nearest neighbor atom around the central atom, CN(i) is the common coordination number of the i-th atom, that is, the number of the nearest neighbors around the i-th atom, CN max is the maximum coordination number; b) Preparation of low-component ammonia-free impregnated activated carbon adsorbent b1) Based on the mass of the porous activated carbon carrier, weigh a certain amount of active components, add them into deionized water and stir them thoroughly to dissolve, then add the porous activated carbon and stir evenly; b2) preparing a sodium borohydride solution, adding it dropwise to the solution in step b1), and stirring at room temperature for 1-4 hours, then filtering the activated carbon and washing it with deionized water for 1-3 times, and then drying; b3) The dried impregnated activated carbon is washed with nitric acid solution for 1-3 times and then washed with deionized water until neutral, and then dried to obtain a low-component ammonia-free impregnated activated carbon adsorbent of CNCl.
2. The method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl according to claim 1, characterized in that: In step a), the Cu surface and the step surface of Au are determined to be suitable substrates for the hydrolysis of cyanogen chloride.
3. The method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl according to claim 2, characterized in that: In step b1), the active component is copper nitrate or chloroauric acid, wherein the amount of copper nitrate added is 3%-10% of the mass of the porous activated carbon carrier, and the amount of chloroauric acid added is 1%-2% of the mass of the porous activated carbon carrier; the amount of deionized water is 400%-1600% of the mass of the porous activated carbon carrier.
4. The method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl according to claim 2, characterized in that: The concentration of the sodium borohydride solution in step b2) is 0.5 mol / L, and the volume ratio of the sodium borohydride solution to the mixed solution in step b1) is 25-100:
1.
5. The method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl according to claim 2, characterized in that: The drying conditions in step b2) and step b3) are both 60-80° C. for 12-24 hours.
6. The method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl according to claim 2, characterized in that: The concentration of the nitric acid solution in step b3) is 1 mol / L.
7. The method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl according to claim 3, characterized in that: In step b1), the active component copper nitrate is replaced by copper sulfate, copper acetate or copper chloride.
8. The method for preparing a low-component ammonia-free impregnated activated carbon adsorbent of CNCl according to claim 1, characterized in that: The porous activated carbon is wood activated carbon, coal-based activated carbon, asphalt-based spherical activated carbon or phenolic resin-based activated carbon.
Citation Information
Patent Citations
Green preparation method of ammonia / chromium-free impregnated activated carbon adsorbent for protecting HCN / CNCl
CN113648970A
Chromium-free impregnated activated carbon for adsorption of toxic gases and / or vapors
US5063196A